Effect of Amoxicillin and Azithromycin Suspensions on Microhardness of Sliver Reinforced and Nano Resin-Modified Glass Ionomers: An In Vitro Study - Zainab R Hasan; Noor R Al-Hasani; Maha Abdulkareem Mahmood; Ali I Ibrahim (Wolters Kluwer Medknow Publications, 2023)
Introduction: We aimed to examine the effect of amoxicillin and azithromycin suspensions on the microhardness of sliver-reinforced glass ionomer and nano-resin modified glass ionomer (GI). Method: Thirty discs (2 mm height x 4 mm diameter) of each type of GI were prepared, which were randomly assigned to amoxicillin, azithromycin, and artificial saliva groups. Microhardness was evaluated by Vickers hardness test before and after three immersion cycles. Results: The overall model (P <  0.001), before/after intervention (P <  0.001), intervention group (type of antibiotic) (P = 0.013), and type of glass ionomer (P <  0.001) showed significant differences among study groups (P <  0.001). Post hoc test showed only non-significant before/after difference for Azithromycin and artificial saliva (control) groups regarding nano resin-modified GI. Conclusion: We found significant microhardness loss for sliver reinforced GI in comparison to nano resin-modified GI after the immersion cycles. Yet, sliver reinforced GI would have higher level of microhardness than nano resin-modified GI after the immersion cycles. Longer time studies are required to assess trend of microhardness loss.